2003
DOI: 10.1021/om0208624
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Phosphinidene Complexes CpR(L)MPAr of the Group 9 Transition Metals Cobalt, Rhodium, and Iridium. Synthesis, Structures, and Properties

Abstract: Novel terminal rhodium-and cobalt-complexed phosphinidenes, Cp*(PR 3 ) and Cp(PPh 3 )CodPAr (8), were obtained by dehydrohalogenation of the primary phosphine complexes Cp*RhCl 2 (PH 2 Ar) (2) and CpCoI 2 (PH 2 Ar) (7) in the presence of a phosphine. X-ray crystal structures are reported for Cp*(PPh 3 )RhdPMes* (3) and Cp(PPh 3 )CodPMes* (8). A comparative reactivity study and a computational survey were performed on the Co-, Rh-, and Ir-containing phosphinidene complexes. All react with organic dihalides to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
66
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 41 publications
6
66
1
3
Order By: Relevance
“…The metal ± ligand BDE for 4 strongly resembles that of previously reported IrÀCO bonds in similar phosphinidene complexes, [Cp(CO)IrPH]. [10] However, the IrÀCO bond length is much shorter (1. . Again, the diagonal C ± P relationship [15] in the Periodic Table is stressed, whereas the vertical N ± P relationship is much less pronounced.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The metal ± ligand BDE for 4 strongly resembles that of previously reported IrÀCO bonds in similar phosphinidene complexes, [Cp(CO)IrPH]. [10] However, the IrÀCO bond length is much shorter (1. . Again, the diagonal C ± P relationship [15] in the Periodic Table is stressed, whereas the vertical N ± P relationship is much less pronounced.…”
supporting
confidence: 80%
“…[9,10] A unique aspect of these novel complexes concerns the facile variation of stabilizing ligand L. So far, established ligands such as phosphines, arsines, phosphites, isocyanides and carbon monoxide have been introduced successfully, leading to stable, isolable complexes with strong metalÀligand bonds. [10] This encouraged us to investigate the availability of phosphinidene complexes that contain an N-heterocyclic carbene ligand, and to study their structural and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…39 Such reactions parallel the properties of transient electrophilic phosphinidenes [(CO) 5 WdPR] as demonstrated by Mathey. 36 Theoretical (DFT) studies of terminal phosphinidene complexes have shown that the character (nucleophilic, electrophilic) of the phosphinidene fragment can be influenced by the metal fragment, particularly the donor or acceptor properties of the ligands and the substituents on the phosphorus atom.…”
mentioning
confidence: 64%
“…They are thermally stable, despite in some notable cases, such as the Re and Co compounds, the lack of sterically encumbered substituents on the metal or phosphorus ligand. The thermal stability of [Re(CO) 5 -{P(N i Pr 2 )}} þ compared to the reported instability of the isoelectronic [W(CO) 5 (PR)] is particularly notable. Clearly it would seem that electronic factors, including the presence of donor substituents on the nonmetal, are responsible for the enhanced stability of the Re cation.…”
Section: ' Introductionmentioning
confidence: 93%
See 1 more Smart Citation